(untitled) (Journal of the College of Basic Education, 2022)
This paper deals with: Rulings dying person in Islamic jurisprudence, and the reason for choosing this topic Because people desperately need to know his rulings. The introductory section deals with: Definition of a dying person, and its signs, and cases, and what does to him, and ruling on his repentance. The first section deals with: The sayings of the jurists in the ruling on the actions of the dying person in financial transactions in buying, selling and the giveaway. The second section deals with: The sayings of the jurists in how to pray the dying person, and how to pay zakat for the dying person. While The Third section deals with: The sayings of the jurists in the ruling on the actions of the dying pe